BIOEXTRACTION OF IRON THROUGH Bacillus sp. SP10 FROM MINERAL OXIDE AND ITS APPLICATION AS PLANT MICRONUTRIENT (Applied Biological Research, 2024)
Iron is an essential micronutrient for all living organisms because of its critical  role in metabolic processes. In plants it plays a key role in the synthesis of  chlorophyll, some vital enzymatic and metabolic processese. However, most of  the iron in nature is present as precipitates or in insoluble forms. Therefore,  biological mechanism has been employed to mineralize Fe(III) oxides into  Fe(II) through microbial action to increase the availability of soluble iron. An iron reducing bacterial strain was isolated based on its tolerant limits and iron  mineralizing ability. The strain Bacillus sp. SP10 effectively mineralized iron  in synthetic medium possessing 1% starch and pH 7. In a 25 day’s column  study, the soluble Fe(II) as micronutrient showed a gradual increase in each  seepage collected from different treatment columns. Similarly, the plants  grown on soil obtained from treatment D (i.e. 1% starch + 1% Bacillus sp.  SP10 inoculum + 0.25% anthraquinone-2,6-disulphonate) column displayed good growth and maximum shoot length, mainly due to the increased  accessibility of iron through microbial mineralization. The mineralization of  Fe in soil was established through SEM and EDX analysis.
Keywords: Bacillus sp; column study; ferric hydroxide; iron mineralization